PENGARUH KOMPENSASI NON FINANSIAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. PENGELOLA SUKARAMAI PEKANBARU - Halfy Resky; Dewita Suryati ningsih; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The study was conducted at PT. Pengelola Sukaramai Pekanbaru. Aims to determine the effect simultaneously and partially Nonfinancial Compensation and Job Satisfaction on Employee Performance PT. Pengelola Sukaramai Pekanbaru. There are three variables: the dependent variable and two independent variables. The study was conducted with a sample of 82 people. The study used multiple regression analysis test tool and using cluster by giving questionnaires to the respondents. In terms of data analysis, using qualitative and quantitative methods using SPSS (Statistical Package for Social Sciences) version 20.0. The analysis showed that the variables Nonfinancial Compensation and Job Satisfaction jointly affect the Employee Performance PT. Pengelola Sukaramai Pekanbaru significant business with 0.000. The influence of the variable compensation partially Nonfinancial, and Job Satisfaction on Employee Performance PT. Pengelola Sukaramai Pekanbaru. The most influential variable most strongly to Employee Performance PT. Pengelola Sukaramai Pekanbaru is variable job satisfaction.Keywords: Non Financial Compensation,Job Satisfaction and Employee Performance